(untitled) (South East Asia Journal of Public Health, 2015)
Heavy vehicle crash rates are high in Sri Lanka. International studies showed that fatigue and day time sleepiness are linked to heavy vehicle crashes. The aim of this study is to examine the level of fatigue, day time sleepiness and their associated factors among heavy vehicle drivers in Sri Lanka. A descriptive cross-sectional study was carried out in 403 heavy vehicle drivers through an interviewer administered structured questionnaire consisting of the Fatigue Severity Scale (FFS) and the Epworth Sleepiness Scale (ESS). The mean age of the study sample was 36.5±8.6 years and all were males. They drive an average of 129.03±87.24 km/day. It was found that the mean FFS score in the study participants was 2.43±0.99 and the mean ESS score was 6.57±4.07. Prevalence of fatigue (FSS score ?4) was 8.7% (n=35) and the prevalence of excessive day time sleepiness (EDS) (ESS score ?10) was 14.4% (n=58). Working for non-fixed schedule, married marital status, and working more than 11 hours/day are found to be significant risk factors for being fatigue. Drivers who were having night sleep of less than 6 hours were found to have a higher risk of EDS. A high prevalence of fatigue (8.7%) and EDS (14.4%) among heavy vehicle drivers was found which may link to heavy vehicle crashes. The occupational health service providers should be aware of the possibility of fatigue and daytime sleepiness in heavy vehicle drivers and its overall risk on the roads to take neces-sary actions. DOI: http://dx.doi.org/10.3329/seajph.v4i1.21832 South East Asia Journal of Public Health Vol.4(1) 2014: 9-16